ANALYSIS OF CUSTOMER SATISFACTION IN PURCHASING TRADITIONAL SERUNI BEVERAGE PRODUCTS ONLINE AT STIE SEMARANG STUDENTS - Sukarsono, Sukarsono; Musfiyana, Risma (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Traditional drinks are drinks that are formulated with ingredients that can nourish the body. This method is to analyze the effect of Product Quality, and Customer Satisfaction on Purchasing Decisions. The subjects in this method were 50 respondents who had previously purchased traditional seruni beverage products in the Semarang city area. In analyzing this research data the methods used include classical assumptions, F and t tests, coefficients of determination and all using SPSS. The results of the classical assumption test show normal data, no heteroscedasticity and no multicollinearity. Then the results of multiple regression analysis showed that regression models can be used to predict buyback decisions based on t-tests. It can be concluded that product quality data and customer satisfaction have significant value because < 0.05 so the hypothesis is accepted. In conclusion, there is a positive and significant influence of data, product quality, and customer satisfaction on purchasing decisions. Buy back the Traditional Seruni Drink product online at Stie Semarang Students. Keywords: customer satisfaction; Product Quality; Purchasing Decision